Comparison of right ventricular function after ministernotomy and full sternotomy aortic valve replacement: a randomized study. (8th January 2018) - Dalén, Magnus; Oliveira Da Silva, Cristina; Sartipy, Ulrik; Winter, Reidar; Franco-Cereceda, Anders; Barimani, Jasmin; Bäck, Magnus; Svenarud, Peter
Abstract: OBJECTIVES: Right ventricular (RV) function is impaired after cardiac surgery, possibly because of the opening of the pericardium. In minimally invasive aortic valve replacement, the pericardium is only partially incised. METHODS: A randomized trial compared RV function after ministernotomy versus full sternotomy in 40 adults undergoing aortic valve replacement at the Karolinska University Hospital. Primary outcomes were tricuspid annular plane systolic excursion, RV pulsed-wave tissue Doppler velocity, RV fractional area change and basal and mid-RV transversal diameters on postoperative Days 4 and 40. RESULTS: On postoperative Day 4, the tricuspid annular plane systolic excursion had decreased in both groups [ministernotomy: median (Q1–Q3) 25 (21–28) vs 16 (11–18), P < 0.001; sternotomy: 22.5 (22–22.5) vs 8 (7–12) mm, P < 0.001] but was higher in the ministernotomy group ( P < 0.001). Pulsed-wave tissue Doppler RV velocity decreased significantly in patients who underwent sternotomy [10.5 (10–12) vs 6.5 (5–8) cm/s, P < 0.001] but did not decrease significantly in patients who underwent ministernotomy [11.5 (11–12) vs 10 (9–11) cm/s, P = 0.054]. Fractional area change was equally decreased in both groups [ministernotomy: 46 (39–51) vs 38 (34–44)%, P < 0.001; sternotomy: 45 (40–49) vs 37 (25–39.5)%, P = 0.003]. RV dimensions did not change on postoperative Day 4 in both groups. The differences between the 2 groups were similar 40 days postoperatively. CONCLUSIONS: RV long-axis function was reduced after both ministernotomy and full sternotomy aortic valve replacement, but the reduction was more pronounced in the full sternotomy group. Global RV function was equally impaired in both groups postoperatively. Clinical trial registration: http://www.clinicaltrials.gov . Unique identifier: NCT01972555.